Risk factors, phenotypic and genotypic characterization of carpabenem resistant Enterobacteriaceae in Tanta University Hospitals, Egypt - amer, wesam hatem; Khalil, Haidy Samir; Abd EL Wahab, Marwa Ahmed (International Journal of Infection Control, 2016)
Carpabenem resistant Enterobacteriacae (CRE) is an increasing worldwide health problem with excess morbidity and mortality. So the aim of this work to study the risk factors, phenotypic and genotypic characters of CRE in our institute. Seventy five patients with hospital acquired infection were enrolled in this study. Identification and susceptibility testing were performed. The differentiation of the types of carbapenemases was done by inhibitor-based tests. The bla genes were detected by using the multiplex PCR. Out of 75 cases of Enterobacteriaceae, 47 (62.7%) CRE were detected. Cases of septicaemia and ventilator associated pneumonia with previous history of carbapenam intake especially in neonatal ICU were more risky for CRE. The overall detection rate in the CRE by modified hodge test (MHT) was 82.9%. By synergy combined disc tests, 47%, 19.1% were positive respectively for Klebsiella pneumonia carbapenemase (KPC) and metallo-β-lactamases (MBLs). By multiplex PCR, the most prevalent gene was bla KPC (22 ,46.8%), followed by blaVIM (10 , 21.3%) , blaOXA-48 (6 , 12.7%), bla KPC + blaOXA-48 (5, 10.6%), bla KPC + blaVIM (3 , 6.4%) while blaIMP and blaNDM genes were not detected. As the burden of carbapenem resistance in Egypt is increasing with limited treatment options. We suggest to develop antimicrobial stewardship in Tanta University Hospital together with governmental supervision to prevent the unrestricted anti microbial sales without prescriptions.